THE CONCEPT OF A DANCE LESSON FOR PROMOTION OF WELL-BEING OF ADULTS - Zīsberga, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The context of the Covid-19 pandemic has highlighted the idea of improving the quality of life and health of people in the context of modern research. If a person is satisfied with himself, has self-realized, with a good physical well-being, he feels satisfied with life in general, thus promoting a quality of life for himself. There is an ageism perception in society that dance classes are suitable for young people. However, when forms of artistic expression are used to promote well-being in adults, it gains an existential dimension. Dance learning in this interpretation includes internalization of body management and dance technique, self-efficacy, positivity, and self-awareness. Therefore, studies focused on the positive effects of dance lessons on mental and physical health in adults are leading to increased interest, thereby contributing to promotion of well-being and healthy ageing. The aim of this publication is to identify the components of well-being in adult dance classes in the context of lifelong learning and to formulate the concept of dance classes. The study data were analysed using the qualitative data processing program NVivo 12.0. As a result, the components of the well-being of dance class participants have been identified, and an explanation of the individual dynamic balance of well-being content within the homeostasis approach is offered, which is the basis of the pedagogical concept.